The effect of footcore stability exercise therapy on increasing range of motion and functional walking ability in cerebral palsy children - Abdullah, Khabib; Swandari, Atik; R, Ichlasul Amalia; Q, Nadhifa Putri (Institute of Computer Science (IOCS), 2024)
Cerebral Palsy (CP) is a permanent disorder in the development of movement and posture in children. One of the movement problems in children with CP is stiffness of the soleus muscle which results in a tiptoe position. This position will make it difficult for the child to stand and walk, thereby reducing the child's functional and movement abilities. This research was conducted to determine the effect of providing foot core stability training therapy on increasing the range of motion of the ankle dorsi flexion joint and increasing the functional ability to walk in children with CP. This research is a field experimental one group pre and post test design. The sample was 15 children with CP at the AzZaki inclusion foundation in Surabaya, who were given foot core stability exercise therapy intervention 10 times in a row for 10 days. The ankle dorsiflexion range of motion was measured with a gonometer and functional walking ability with GMFM (gross motor function measurement). Research Results is there was a mean increase in ankle LGS towards dorsi flexion of 3.2° (p=0.001) and a mean increase in walking ability with GMFM measurements of 11.2% (p=0.00).